Implementasi MBKM Magang : Pelaksanaan Agregator Musik Digital di PT Alcor Karya Gemilang - David Kartono; Koerniawan Hidajat (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
This activity aims to analyze the operational process of digital music distribution at the company level, as well as the role of metadata management and publishing administration in supporting the effectiveness of musical distribution. The main problem studied is how metadata accuracy, publishing system integration, and streaming data utilization affect the smoothness of digital music distribution. The method used is a qualitative descriptive approach through direct observation, operational involvement, and documentation of the digital music distribution work process at PT Alcor Karya Gemilang through the Inside Indo label. The results of the activity show that metadata functions as a digital identity of the work that determines the algorithmic indexing process and automatic royalty distribution. The integration of publishing administration improves the legality and efficiency of content validation, while streaming data analysis becomes the basis for promotional decisions and further distribution strategies. Operational constraints such as the need for high accuracy and understanding of technical terms indicate the importance of digital literacy in digital music distribution. The conclusion of the activity confirms that digital music distribution is a data-based system that integrates technical, administrative, and managerial aspects, and has a strategic role in supporting independent musicians to enter the global streaming platform ecosystem legally and systematically.